MO399: Remodel: A Mechanistic Trial Evaluating the Effects of Semaglutide on the Kidneys In People With Type 2 Diabetes and Chronic Kidney Disease. (3rd May 2022) - Bjornstad, Petter; Cherney, David; Lawson, Jack; Møntegaard, Camilla; Pruijm, Menno; Tuttle, Katherine; Vrhnjak, Blaz; Kretzler, Matthias
Abstract: BACKGROUND AND AIMS: Approximately 40% of people with type 2 diabetes (T2D) develop chronic kidney disease (CKD) and, despite current treatment, T2D is the most common cause of progression to kidney failure. This situation underscores the need for additional pharmacotherapeutic options. Analyses of cardiovascular outcomes trials suggest that glucagon-like peptide-1 receptor agonists (GLP-1RAs), such as semaglutide, lower albuminuria and attenuate estimated glomerular filtration rate (eGFR) decline in people with T2D. Previous analyses suggest that GLP-1RAs reduce hypoxia and inflammation and, thereby, have a mode of action on the kidneys that is distinct from other treatments, such as sodium-glucose cotransporter-2 (SGCT-2) inhibitors and renin–angiotensin–aldosterone system (RAAS) blockers. Furthermore, the primary benefit of semaglutide appears to be in people with an eGFR < 60 mL/min/1.73 m 2, a group in which there is a significant residual risk of progression and a consequent unmet need for effective treatment. To gain further insights on the kidney-protective mechanism of action of semaglutide, the REMODEL trial is integrating investigative functional kidney magnetic resonance imaging (MRI) and kidney biopsies; recent developments in these techniques permit elucidation of the mechanisms underlying kidney protection with current therapies. Mechanistic findings of the REMODEL trial will complement those of the ongoing FLOW clinical trial, which is designed to evaluate clinical outcomes in people with T2D and CKD treated with once-weekly (OW) subcutaneous semaglutide. METHOD: REMODEL (NCT04865770) is a 52-week, multicentre, international clinical trial (Figure 1 ). Primary endpoints are MRI-based and include change from baseline to week 52 in kidney oxygenation (measured with BOLD MRI R2*), global kidney perfusion (phase-contrast MRI) and kidney inflammation (T1 Mapping MRI). Secondary endpoints evaluated from kidney biopsies in a nested cohort ( n ∼ 45) include change from baseline to week 52 in intrarenal mRNA expression, assessed by single-nucleus transcriptomics and glomerular basement membrane width, assessed by morphometry. Other secondary endpoints include the apparent diffusion coefficient (estimating renal fibrosis; evaluated with diffusion-weighted MRI), natriuresis, albumin excretion rate and creatinine clearance. MRI outcomes will also be evaluated at week 4 to identify potential early effects of semaglutide in the kidney. Examples of MRI and kidney biopsy single-cell gene expression profile data from participants with CKD are shown in Figure 2 (data not from REMODEL). Safety will be assessed throughout the trial. RESULTS: REMODEL was initiated in April 2021 and is being conducted in Canada, France, Italy, Poland, South Africa, Spain and USA. CONCLUSION: REMODEL will investigate the effect of the GLP-1RA semaglutide on inflammatory and hypoxia-related pathways in the kidney. The combination of MRI and tissue-level interrogation with biopsies will complement standard laboratory findings, enabling the identification of cells and pathways involved in kidney disease and protection. The trial will provide valuable mechanistic insights on the use of OW semaglutide in people with T2D and CKD and may stimulate the development of a precision medicine approach to the management of such individuals. In addition, REMODEL will complement the findings of the FLOW trial.